O cidadão legislador: iniciativa popular de emenda constitucional no Estado Democrático de Direito - Gonçalves Junior, Jerson Carneiro (2012)
The objectives of this paper are to reflect upon the exercise of the political fundamental right of citizen s initiative. In order to fulfill this constitutional aspiration under the scope of citizenship and the democratic rule of law, it is essential to consider the concept of citizenship and the analysis of citizen s initiative in the federal, state, district. The legal system points out to the fundamental principle of citizenship and the democratic rule of Law, communicating constitutional laws implied in the process of the exercise of citizenship, disseminating them throughout the legal system. Based on the idea of principle, this paper analyzes citizen s initiative expressed in the federal, state and municipal realms in order to sustain the feasibility of the right to exercise this fundamental political right in the lawmaking process for constitutional amendments. In order to do that, in the light of constitutional law, there is the need to recognize the innate citizen as the only one entitled to propose and initiate amendments to the Constitution. In this sense, constitutional law is an open inter-text and the study of history is fundamental, because without it human beings would never have found conditions to evolve. For this reason, the path to understand citizen s initiative should consider the Brazilian constitutional history, especially the review of the Assembly s annals of the 1987 National Constitution Assembly in order to evaluate and challenge the writing of the constitutional and infra-constitutional laws related to citizen s initiative in order to demonstrate, by the interpretation of constitutional laws, that innate citizens have the possibility of exercising their political fundamental right in relation to the lawmaking process and constitutional amendments